Analisis Jaringan Sosial Untuk Penguatan Komunikasi Petani Pembibitan Sayuran (Studi Kasus: Desa Wangunsari Lembang Bandung Barat) - Azifah An'amillah; Mia Rosmiati; Pujo Hutomo (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Buton, 2023)
Wangunsari Village is a pioneer village that initiated a vegetable nursery as a business unit. In developing vegetable nurseries, nursery farmers face various problems. To solve problems, nursery farmers rely only on personal experience and information they have. With regard to information, communication is very much needed for the development of vegetable nursery farming. To strengthen the communication of vegetable nursery farmers in Wangunsari Village, this study uses social network analysis to find out community features and key actors. The measurements used are density, efficient clustering, degree centrality, closeness centrality, betweeness centrality, and eigenvector centrality. In the measurement of density, the strength of the network is 11.5% with 129 bonds. Clustering measurement coefficient with a value of 0.569. As for the degree centrality measurement, namely InDeg and Outdeg by 10% for actor H. Closeness centrality, namely InCloseness is 66 and InFarness 50 is owned by actor H. Betweenness centrality is highest at 682.35 for actor H. value 0.4. The existence of this social network analysis can be the first step for agricultural extension workers and other institutions in agricultural development efforts regarding the development of vegetable nurseries in Wangunsari Village.